Morphology and Phase Composition of Gelatin-Starch Blends - Liu, Xing-xun; Wang, Yan-fei; Zhang, Nuo-zi; Shanks, Robert A.; Liu, Hong-sheng; Tong, Zhen; Chen, Ling; Yu, Long (Chinese journal of polymer science, 2014)
Morphology and phase compositions of different starch-gelatin blends were investigated by various microscopes： optical, SEM and synchrotron FTIR microscopy. A high amylose （80%） corn starch, grafted with hydroxypropyl to enhance flexibilty and hydrophilicity, and plasticized by poly（ethylene glycol） （PEG）, was used in this work. SEM revealed that the surface became smoother after adding PEG. Optical microscopy observation revealed that compatibility between gelatin and starch was improved by adding PEG. An FTIR beam focused on a 5 ~tm x 5 ~tm detection area by the micro-spectroscope was used to map chemical composition. The ratio of areas of the saccharide bands （1180-953 cm-1） and the amide I and II bands （1750-1483 cm-1） was used to monitor the relative distributions of the two components in the blends. The FTIR maps indicated that gelatin constituted the continuous phase up to 80% of starch content. All of the FTIR spectra showed contributions from both starch and gelatin absorptions, therefore indicating that complete demixing with pure starch and gelatin domains did not occur. The PEG improved the compatibility of the gelatin-starch blends.